2019
DOI: 10.1111/are.14253
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas veronii caused disease and pathological changes in Asian swamp eel Monopterus albus

Abstract: More and more diseases were occurred in the aquaculture of Asian swamp eel. Bacterial isolates were collected from the pathogenic organs of diseased Asian swamp eels. A dominant strain, Aeromonas veronii JL‐01, was isolated and identified from the liver and intestine tissue of diseased Asian swamp eels. The symptoms of fish infected artificially with A. veronii were the same as those observed under natural infection. The mortality rate was 40%–80% and infected Asian swamp eels died 2–3 days after infection. Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
12
0
2
Order By: Relevance
“…Here, dietary Val signi cantly improved the SR after infection with A. veronii, which suggested that dietary Val might improve disease resistance. The intestine is one of the target organs of A. veronii, which causes damage to the intestinal anatomy [49]. In this study, dietary Val alleviated intestinal injury after infection with A. veronii.…”
Section: Dietary Val Improved Intestinal Antioxidant Capacity Via Nrf2 Signaling Pathway After Infection With a Veroniimentioning
confidence: 69%
See 1 more Smart Citation
“…Here, dietary Val signi cantly improved the SR after infection with A. veronii, which suggested that dietary Val might improve disease resistance. The intestine is one of the target organs of A. veronii, which causes damage to the intestinal anatomy [49]. In this study, dietary Val alleviated intestinal injury after infection with A. veronii.…”
Section: Dietary Val Improved Intestinal Antioxidant Capacity Via Nrf2 Signaling Pathway After Infection With a Veroniimentioning
confidence: 69%
“…Although ROS are normally produced during intracellular physiological reactions, excess production accompanied by insu cient elimination results in protein oxidation and lipid peroxidation that cause structural damage to the cells and, in turn, to the intestinal epithelium. Previous studies showed that A. veronii infection led to ROS overproduction [15,[49][50][51]. The degree of protein oxidation and lipid peroxidation can be re ected by the PC and MDA concentrations, respectively [52].…”
Section: Dietary Val Improved Intestinal Antioxidant Capacity Via Nrf2 Signaling Pathway After Infection With a Veroniimentioning
confidence: 99%
“…At present, though artificial propagation of rice field eel has been successfully practised, its larvae for artificial culture have been mainly supplied from wild resource (Guan, Zhou, Cui, & Feng, 1996). During the intensive cage‐culture conditions, harmful diseases from parasitic, bacterial and viral infections could often result in great economic losses of aquaculture producers (Liu et al., 2019; Shao et al., 2016; Xia et al., 2019). It is necessary that high‐quality breeds would be screened or cultivated to meet the aquaculture producers’ demands.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore concluded that the three strains possess significant differences at growth rate, fecundity and nutritive composition. Up to now, studies on the rice field eel have been mainly focused on molecular mechanisms of sex reverse (Cai et al., 2017; Gao, Dan, Hu, & Li, 2016; He et al., 2014; Sheng et al., 2015), population genetics (Cai et al., 2008; Li, Sun, Fan, & Zhang, 2013; Liang, Guo, Li, Luo, & Zou, 2016), disease (Liu et al., 2019; Shao, Yuan, Shen, Hu, & Gu, 2016; Xia et al., 2019) and immune genes (Gao et al., 2019; Tang et al., 2019; Xu et al., 2016). Limited information of molecular mechanism, however, was available on the differences at growth rate, fecundity and nutritive composition among the three strains with different body colours.…”
Section: Introductionmentioning
confidence: 99%
“…D-59 bacterial solution (100 μL) was spread evenly on a CAMHB agarose plate using a sterile applicator stick. After the medium was dried, drug-sensitive paper sheets were placed on the agar surface and the plates were incubated at 28°C for 24 h. The diameter of the inhibition circle around each drug‐sensitive paper sheet was measured using vernier calipers ( Xia et al., 2019 ). The susceptibility of the strains to the antibiotics was evaluated by the diameter of the bacterial inhibition circle with reference to the drug sensitive paper sheet instructions ( CLSI, 2018 ).…”
Section: Methodsmentioning
confidence: 99%